Karyotype of the cricket, Zucchiella atlantica, with an overview of the chromosomes of the subfamily Nemobiinae - Portugal, C. B.; Mesa, A. [UNESP] (Univ Arizona, 2007)
Few reports have been published on cytogenetics in crickets of the subfamily Nemobiinae. Within the Neotropical region the karyotypes of only two species are known, both of them belonging to the genus Phoremia. In the present paper, chromosomes of a third Neotropical species, Zucchiella atlanticaMello 1990 (Orthoptera: Trigonidiidae), have been studied and a cytological review of other species of that subfamily is presented. Zucchiella atlantica shows 2n male = 22 + XO and 2n female = 22 + XX which suggests an ancestral condition within the subfamily as the diploid number in all the species previously studied ranges from 2n male = 7 to 2n female = 21. In Orthoptera those species with high chromosome numbers tend to show reduction in their chromosomal numbers by means of centric fusions rather than to increase chromosomal numbers, due to difficulties in the availability of new centromeres. A structural polymorphism in one chromosome of pair 5 was observed as an intra-individual variation, suggesting differential activity of the genome from cell to cell.